Gene expression differentials driven by mass rearing and artificial selection in black soldier fly colonies. Issue 2 (24th November 2022) - Hull, Kelvin L.; Greenwood, Matthew P.; Lloyd, Melissa; Bester‐van der Merwe, Aletta E.; Rhode, Clint
Abstract: The micro‐evolutionary forces that shape genetic diversity during domestication have been assessed in many plant and animal systems. However, the impact of these processes on gene expression, and consequent functional adaptation to artificial environments, remains under‐investigated. In this study, whole‐transcriptome dynamics associated with the early stages of domestication of the black soldier fly (BSF), Hermetia illucens, were assessed. Differential gene expression (DGE) was evaluated in relation to (i) generational time within the cultured environment (F2 vs. F3), and (ii) two selection strategies [no artificial selective pressure (NS); and selection for greater larval mass (SEL)]. RNA‐seq was conducted on 5th instar BSF larvae ( n  = 36), representing equal proportions of the NS (F2 = 9; F3 = 9) and SEL (F2 = 9; F3 = 9) groups. A multidimensional scaling plot revealed greater gene expression variability within the NS and F2 subgroups, while the SEL group clustered separately with lower levels of variation. Comparisons between generations revealed 898 differentially expressed genes (DEGs; FDR‐corrected p  < 0.05), while between selection strategies, 213 DEGs were observed (FDR‐corrected p  < 0.05). Enrichment analyses revealed that metabolic, developmental, and defence response processes were over‐expressed in the comparison between F2 and F3 larvae, while metabolic processes were the main differentiating factor between NS and SEL lines. This illustrates the functional adaptations that occur in BSF colonies across generations due to mass rearing; as well as highlighting genic dynamics associated with artificial selection for production traits that might inform future selective breeding strategies. Abstract : Differentially expressed genes across generations illustrated that the F3 group had greater expression of metabolic and development‐related genes, as well as lower expression of defence response genes. Metabolic processes were the main differentiating factor between non‐selected and selected larvae, indicating that the selected group was likely larger due to increased expression of metabolism‐related genes. Numerous genes displayed low to moderate Pearson's correlation coefficients, indicating that many genes have small, additive effects in relation to larval mass and growth.